The role of Public Health resources in coping and treating COVID-19 - Jose L. Vilchez (Revista Cubana de Medicina Militar)
Introduction: The COVID-19 crisis has put the management of various political systems to the test. There is possibly nothing more evident than the number of infected and deaths in a country as an index of the effectiveness of politicians in coping a crisis. The citizen is a customer. They pay their taxes and they have all the right to demand their politicians to be efficient in protecting their rights. In this sense, there is no right above the right to life. Some governments have attempted to shift the focus of their responsibility on the public health state budgets of previous governments, as an excuse for its catastrophic management. Objective: This work precisely analyzes whether there is any statistically significant relationship between the budget dedicated to public health services and the number of infected and deaths by COVID-19. Methods: A non-parametric analysis of Kendall's Tau b was carried out for Public Health Expenditure (both public and private investment) and the number of COVID-19 infections (in 178 countries) and deaths (in 162 countries; provided by John Hopkins University). Results: Results showed that there is not only a negative relationship (between higher spending on health and fewer affected people) but, surprisingly, there is a positive relationship between these variables. Conclusions: One possible hypothesis is that the fact of having a health system with more resources makes politicians be more confident when facing health crisis.